A novel solution for ground reaction curve of tunnels in elastoplastic strain softening rock masses - Ghorbani, Ali; Hasanzadehshooiili, Hadi (Journal of Civil Engineering and Management, 2017)
Ground Reaction Curve (GRC) is one of the most important elements of convergence-confinement method generally used to design tunnels. Realistic presentation of GRC is usually assessed based on the advanced rock strength criteria, also, rock mass behavior (including plasticity and softening treatments). Since taking these parameters into account is not simply possible for practitioners and needs complicated coupled theoretical-numerical solutions, this paper presents a simple novel approach based on Evolutionary Polynomial Regression to determine GRC of rock masses obeying both Mohr-Coulomb and Hoek-Brown criteria and strain softening behaviors. The proposed models accurately present support pressures based on radial displacement, rock mass strength and softening parameter (determination coefficient of 97.98% and 94.2% respectively for Mohr-Coulomb and Hoek-Brown strain softening materials). The accuracy of the proposed equations are approved through comparing the EPR developed GRCs with the ground reaction curves available in the literature. Besides, the sensitivity analysis is carried out and in-situ stress, residual Hoek-Brown’s m constant and residual dilation angle are introduced as parameters with the most influence on the support pressure in Hoek-Brown and peak and residual geological strength index are the most affective parameters on the support pressure of tunnels in the strain softening Mohr-Coulomb rock mass.